2021
DOI: 10.1080/21655979.2021.1890383
|View full text |Cite
|
Sign up to set email alerts
|

Muscleblind-like 1 antisense RNA 1 inhibits cell proliferation, invasion, and migration of prostate cancer by sponging miR-181a-5p and regulating PTEN/PI3K/AKT/mTOR signaling

Abstract: The present study aimed to investigate the role and underlying mechanisms of long non-coding RNA (lncRNA) muscleblind-like 1 antisense RNA 1 (MBNL1-AS1) in the progression of Prostate cancer (PCa). MBNL1-AS1 and microRNA (miR)-181a-5p expression in PCa tissues and several human PCa cell lines were analyzed, respectively, using StarBasev3.0 project and RT-qPCR assay. After MBNL1-AS1 overexpression, cell proliferation, invasion and migration were, respectively, evaluated using CCK-8, colony formation, transwell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Similarly, research has reported that miR-106a-5p can regulate C2C12 myogenesis via repressing the PI3K/Akt pathway [ 46 ]. It is noteworthy that several reports have demonstrated that the PI3K/Akt signaling participated in the regulation of cell proliferation, invasion, and migration in different cancer cells [ 47–49 ], which further provides possible pieces of evidence for the inhibitory effect of miR-106a-5p in EMS via the PI3K/Akt/mTOR signaling pathway. In addition, the main disadvantage of our study is that there are too few cases in the normal group in the clinical sample.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, research has reported that miR-106a-5p can regulate C2C12 myogenesis via repressing the PI3K/Akt pathway [ 46 ]. It is noteworthy that several reports have demonstrated that the PI3K/Akt signaling participated in the regulation of cell proliferation, invasion, and migration in different cancer cells [ 47–49 ], which further provides possible pieces of evidence for the inhibitory effect of miR-106a-5p in EMS via the PI3K/Akt/mTOR signaling pathway. In addition, the main disadvantage of our study is that there are too few cases in the normal group in the clinical sample.…”
Section: Discussionmentioning
confidence: 84%
“…PI3K, a neural signal transduction enzyme, can be activated by tyrosine kinase receptor, G protein-coupled receptor/cytokine receptor, and Ras protein-related GDP enzyme receptor, so that it can promote the proliferation, survival, adhesion, and differentiation of cells participating in the cytoskeletal organization [ 29 , 30 ] . Akt serves as a downstream serine/threonine kinase of PI3k and involves in cell proliferation and differentiation by activating downstream factors HIF-1a and mTOR [ 31 , 32 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of miR-181a-5p inhibited the expression of PTEN and regulated the PI3K/AKT/mTOR signaling pathway [X. 12 ]. It was studied that targeting of MTDH by miR-145-5p or miR-145-3p is associated with PCa prognosis, thereby regulating the growth and metastasis of PCa cells [D. 13 ].…”
Section: Introductionmentioning
confidence: 99%